Cell-Type Specific Development of the Hyperpolarization-Activated Current, Ih, in Prefrontal Cortical Neurons - Yang, Sha-Sha; Li, Yan-Chun; Coley, Austin A.; Chamberlin, Linda A.; Yu, Ping; Gao, Wen-Jun (Frontiers in Synaptic Neuroscience, 2018)
H-current, also known as Ih, is an inward current generated by the hyperpolarization-activated cyclic nucleotide-gated (HCN) cation channels. Ih plays an essential role in regulating neuronal properties, synaptic integration and plasticity, and synchronous activity in the brain. As these biological factors change across development, the brain undergoes varying levels of vulnerability to disorders like schizophrenia that disrupt prefrontal cortex (PFC)-dependent function. However, developmental changes in Ih in PFC neurons remains untested. Here we examine Ih in pyramidal neurons versus GABAergic parvalbumin-expressing (PV+) interneurons in developing mouse PFC. Our findings show that the amplitudes of Ih in these cell types are identical during the juvenile period, but differ at later time points. In pyramidal neurons, Ih amplitude significantly increases from juvenile to adolescence and follows a similar trend into adulthood. In contrast, the amplitude of Ih in PV+ interneurons decreases from juvenile to adolescence, and does not change from adolescence to adulthood. Moreover, the kinetics of HCN channels in pyramidal neurons is significantly slower than in PV+ interneurons, with a gradual decrease in pyramidal neurons and a gradual increase in PV+ cells across development. Our study reveals distinct developmental trajectories of Ih in pyramidal neurons and PV+ interneurons. The cell-type specific alteration of Ih during the critical period from juvenile to adolescence reflects the contribution of Ih to the maturation of the PFC and PFC-dependent function. These findings are essential for a better understanding of normal PFC function, and for elucidating Ih’s crucial role in the pathophysiology of neurodevelopmental disorders.